Al-Qur’an sebagai Sumber Ajaran Islam: Analisis Konseptual dan Kedudukannya dalam Sistem Hukum Islam - Ahmad Mursyiddin; Rahmi Utami; Muhammad Dipa; Utia Nurainis; Yazkia Awalia Riisya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to analyze the position of the Qur'an as the primary source of Islamic teachings and examine its normative and functional dimensions within the Islamic legal system. This study uses a library research approach with qualitative analysis methods on relevant classical and contemporary literature. This study discusses the etymological and terminological meaning of the Qur'an, the gradual process of revelation, and the classification of teachings that include the aspects of i'tiqadiyah, amaliyah, and khuluqiyah. The results show that the Qur'an holds a central position as a normative source that serves as the basis for the formation of theological, legal, and moral systems in Islam. In addition, the various nomenclatures of the Qur'an such as Al-Huda, Al-Kitab, and Al-Furqan reflect its multidimensional function in the lives of Muslims. This study emphasizes the importance of a comprehensive understanding of the Qur'an as the foundation of Islamic teachings in the context of science and life practice